Can Intravenous Injection of Tranexamic Acid Be Used in Routine Practice with Active Management of the Third Stage of Labor in Vaginal Delivery? A Randomized Controlled Study - Gungorduk, Kemal; Asıcıoğlu, Osman; Yıldırım, Gokhan; Ark, Cemal; Tekirdağ, Ali İsmet; Besımoglu, Berhan (American Journal of Perinatology, 2013)
Objective To estimate the effects of adding intravenous tranexamic acid (TA) to the standard active management of third-stage labor to reduce vaginal blood loss during the third and fourth stages of labor.Study Design A prospective, double-blind, equivalence randomized, controlled study was performed. Women were randomly allocated to receive an intravenous infusion of TA (experimental group, n = 228) or 5% glucose (placebo group, n = 226) at delivery of the anterior shoulder. Active management of the third stage of labor, which includes prophylactic injection of 10 IU of oxytocin within 2 minutes of birth, early clamping of the umbilical cord, and controlled cord traction following delivery, was used in both groups. The primary outcome was mean blood loss during the third and fourth stages of labor.Results Mean estimated blood loss at the third and fourth stages of labor was significantly lower in the experimental group than that in the placebo group (261.5 ± 146.8 mL versus 349.98 ± 188.85 mL, respectively; p < 0.001). The frequency of postpartum hemorrhage > 500 mL was also lower in the experimental group (4, 1.8%) compared with that in the placebo controls (15, [6.8%]; relative risk, 3.76; 95% confidence interval, 1.27 to 11.15; p = 0.01). No episode of thrombosis occurred in the women who received TA.Conclusions The use of TA with standard active management of the third stage of labor reduced postpartum blood loss, and no increase in the incidence of thromboembolic events was observed.
Keywords: tranexamic acid; postpartum vaginal blood loss; third and fourth stages of labor